Knowledge Sharing Barriers In A \"Multinational\" Organizational Based In Malaysia - Masaeli, Sara (2011)
This study investigated possible causes of resistance or support by knowledge workers to the sharing of knowledge within an organization by examining individual factors, organizational factors, motivational factors, and technological factors.